Sieviešu Ordinācija Dinamiskā Apziņas Spirālveida Attīstības Pakāpju Perspektīvā: Women Ordination from the Perspective of Stages of Spiral Dynamics Development of Consciousness. - Rozentāls, Linards 1971- (2015)
The process of spiral dynamics in the development process of consciousness is the name of the description of gradual development process that was first described by Clares Graves, Don Beck, Christopher Cowan and Ken Wilber. The stages of development of consciousness are marked with numbers from 1.0 to 9.0 - that name different identities: instinctive, magical, power, rule and role, rational, sensitive, integral, holistic and united. In Latvia, ordination of women was started because of the shortage of pastors, as well as of increasing awareness of new possibilites in the ambient world, which are typical arguments of the level 5.0 - during crisis I choose what is useful, rational, so that ordination gives maximum benefit. Breaking into the sacramentally mythical notion of ordination, opening doors to women, is a typical manifestation of the spirituality of 5.0 level. But ordination of women can grow roots only in such church and society which reflects the values of 6.0 level. When church is able to enter into spirituality of 6.0 which is formed from self-responsible and critically thinking individual of 5.0, leaving behind the fixations at level 4.0, as well as becoming open to rational and transrational levels, only then the changes will happen, that can grow but when readiness and maturity are reached.